1998
DOI: 10.1038/sj.gt.3300547
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer and expression in oligodendrocytes under the control of myelin basic protein transcriptional control region mediated by adeno-associated virus

Abstract: In this study, a rAAV vector carrying a reporter gene,Infusion of approximately 6 × 10 9 particles (2 × 10 5 infec-'humanized' green fluorescent protein (GFP), linked to the tious units) of rAAV-MBP-GFP into mouse brains resulted transcriptional control region from the myelin basic protein in the GFP expression specifically in white matter. The (MBP) gene (a myelin-forming cell-specific gene) was con-GFP protein was detected 15 days later by immunostainstructed. Transduction of oligodendrocytes was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 18 publications
1
65
0
Order By: Relevance
“…However, this assay is biased toward cells in which the CMV promoter is active, and may favor neurons over other cell types such as oligodendrocytes. 12,13 We have also used the scAAV vectors to investigate the limits of rAAV transduction in the liver. Previous studies have shown that hepatocytes are not efficiently transduced by rAAV, the limiting factor apparently being the conversion of the single-stranded vector DNA to duplex by the liver cells.…”
Section: Tr Mutant For Self-complementary Aav Dm Mccarty Et Almentioning
confidence: 99%
“…However, this assay is biased toward cells in which the CMV promoter is active, and may favor neurons over other cell types such as oligodendrocytes. 12,13 We have also used the scAAV vectors to investigate the limits of rAAV transduction in the liver. Previous studies have shown that hepatocytes are not efficiently transduced by rAAV, the limiting factor apparently being the conversion of the single-stranded vector DNA to duplex by the liver cells.…”
Section: Tr Mutant For Self-complementary Aav Dm Mccarty Et Almentioning
confidence: 99%
“…16 In addition, pathological responses may alter the expression profile of neurons or glia, for instance, reactive astrocytes often exhibit an upregulation of GFAP and other cellular factors, which may affect AAV expression using a glial promoter.…”
Section: Figure 3 Aav-2 Injections To Rat Striatum With Three Differementioning
confidence: 99%
“…One advantage of AAV-2 virus for in vivo functional genomic studies is its lack of toxicity, 31 which is related to this paucity of viral elements; infection with AAV-2 in the brain is not known to elicit a systemic immune response, nor is there inflammation or injury in brain regions where the vector has been injected. 5,7,9,16,31 Despite the safety advantage related to minimal native AAV elements, the small packaging capacity of AAV vectors has limited gene transfer applications. Previous studies suggested that up to 6.0 kb can be packaged into virus, but these 'over-sized' viruses were not infectious, 32 hence the common assumption is that the packaged genome must be limited to just 110% of wild-type AAV or no greater than ෂ5.1 kb.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations